(untitled) (International Journal of Food and Nutritional Sciences, 2025)
A vital component of the human diet and a significant source of nutrients are plants. They give us vitamins, protein, carbs, cholesterol-lowering agents, antioxidants, and other vital sources of physiologically active molecules. There is virtually little study on the physiologically active chemicals found in plants, despite the fact that their nutritional worth has been extensively explored